"1st century BCE occurrence of chicken, house mouse and black rat in Morocco: Socio-economic changes around the reign of Juba II on the site of Rirha". (February 2020) - Oueslati, Tarek; Kbiri Alaoui, Mohamed; Ichkhakh, Abdelfattah; Callegarin, Laurent; de Chazelle, Claire-Anne; Rocca, Elsa; Carrato, et Charlotte
Highlights: 1st mention of chicken inland Morocco prior to Roman times. 1st mention of black rat and house mouse in Morocco in 1st century BC. Introduction of House mouse probable in 3rd/2nd c BC prior to the introduction of black rat. Contemporaneous economic and cultural dynamics (pottery, coins, writing, architecture). Mice and rats are relevant proxies to measure the scale of movements of people and goods. Abstract: This paper provides new data on the human-mediated introduction of chicken ( Gallus gallus domesticus Linnaeus, 1758), black rat ( Rattus rattus Linnaeus, 1758) and house mouse ( M. musculus domesticus Schwarz & Schwarz, 1943) on the stratified site of Rirha, located in the Gharb plain, Morocco. The Mauretanian Tell, with its mud brick houses, streets, kitchens and dump areas have been excavated extensively and benefitted of sieving which provided clear evidence of the presence of the galliform and of the two murids in 1st century BCE levels and probably earlier around the 3rd 2nd c BCE for house mouse. This renews our understanding of the phylogeography of these three allochthonous species in Morocco. At a larger scale, our results feed the archaeological understanding of the occupation of this diachronic site and the evolution of the dynamics of trade and exchange prior to the Roman period in this area of northern Africa.